1976
DOI: 10.1039/f19767202685
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid monolayers at non-polar oil/water interfaces. Part 1.—Phase transitions in distearoly-lecithin films at the n-heptane aqueous sodium chloride interface

Abstract: Using compression techniques, surface pressure (II) against area ( A ) isotherms are measured as a function of temperature for insoluble monolayers of 1,2-distearoyl-sn-glycero-3-phosphorylcholine spread at the n-heptane/aqueous sodium chloride interface. Problems of spreading are resolved and accurate results at moderate and high IT are presented. The results show an almost first order phase change which is very temperature sensitive. Various forms of the Clapeyron analysis are applied to the data to calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 0 publications
3
67
0
Order By: Relevance
“…The values of 40.6 Å 3 for the -CH 2 OH volume ͑determined by bulk measurements just above the freezing point 60 ͒ and 30 Å 3 for the volume per bulk water molecule indicate that there is enough space for one water molecule for every 3 alkanol headgroups in layer 1. Including these additional 3 electrons per alkanol from the water that penetrates the headgroup region would raise the values of area per molecule calculated in the previous paragraph to 22.8 Ϯ2 , 23.0 Ϯ1 , 22.8 Ϯ1 , and 23.9 Ϯ1 Å 2 for C 20 OH, C 22 OH, C 24 OH, and C 30 OH. These values are still consistent with an area per alkanol molecule of 23.4 Å 2 .…”
Section: Alkanols At the Water-hexane Interface: Low Temperaturementioning
confidence: 98%
See 3 more Smart Citations
“…The values of 40.6 Å 3 for the -CH 2 OH volume ͑determined by bulk measurements just above the freezing point 60 ͒ and 30 Å 3 for the volume per bulk water molecule indicate that there is enough space for one water molecule for every 3 alkanol headgroups in layer 1. Including these additional 3 electrons per alkanol from the water that penetrates the headgroup region would raise the values of area per molecule calculated in the previous paragraph to 22.8 Ϯ2 , 23.0 Ϯ1 , 22.8 Ϯ1 , and 23.9 Ϯ1 Å 2 for C 20 OH, C 22 OH, C 24 OH, and C 30 OH. These values are still consistent with an area per alkanol molecule of 23.4 Å 2 .…”
Section: Alkanols At the Water-hexane Interface: Low Temperaturementioning
confidence: 98%
“…These results are consistent with values measured by other groups using the pendant drop method to yield ⌬S a ϭ1.7 mJ/m 2 K for C 18 OH and ⌬S a ϭ2.0 mJ/m 2 K for C 20 OH at the water-hexane interface ͑the C 20 OH value was measured for concentrations of both 11.25 and 18.04 mol/kg͒. 17,55 The values of ⌬S a are much larger than the values reported previously for surface freezing at a pure alkanolvapor interface (⌬S a ϭ0.88, 1.15, 1.2, and 1.3 mJ/m 2 K for C 20 OH, C 22 OH, C 24 OH, and C 28 OH, respectively, where these values are half that for freezing of a bilayer in order to facilitate comparison with our monolayer͒. 56 Our values of ⌬S a are also much larger than the values of ⌬S for the bulk rotator-liquid transition ͑measured for the bulk, but here stated for an effective ''monolayer'' of bulk material, ⌬S a ϭ1.09, 1.2, and 1.35 mJ/m 2 K for C 20 OH, C 22 OH, and C 24 OH).…”
Section: G Surface Diffuse Scattering Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Pethica and co-workers [1] measured the surface pressure isotherms for a series of insoluble (distearoyl phosphatidylcholine-DSPC and dioleoyl phosphatidylcholine-DOPC) at the n-heptane/water interface using a Langmuir trough. These authors concluded that DSPC forms monolayers which were affected by the concentration of the aqueous electrolyte (NaCl which concentration is varied between 0.1 and 0.01 M) and by the pH (between 2 and 5).…”
Section: Introductionmentioning
confidence: 99%